Controversy and Voluntarism Among the Elite: An Ethnographic Study of the Sufi Community in Cibingbin, Indonesia - Ayub Wahyudin; Noval Maliki; Hilyatul Auliya; Raharjo, Raharjo; Najahan Musyafak; Mohammad Fahmi bin Abdul Hamid; Muhammad Nurkhanif (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2024)
This article explores the intricate dynamics among Sufi elites in Cibingbin, highlighting the significant tensions within this distinctive group. The Sufi community is deeply divided, engaging in intense debates and frequent confrontations with each other. Central to these disputes are issues surrounding the Nasab dialectics, an ideology associated with the habaib that stresses the concept of voluntarism among the Sufi elite. These internal debates are most intense between the habaib faction, known as Kanzus Sholawat Cibingbin, and the local religious authorities, referred to as Kyai Kampung. As each group digs in and solidifies their doctrinal positions, the struggle for dominance in the public sphere becomes more pronounced. This phenomenon, which aligns with Habermas's theories regarding the legitimacy of power in public spaces, has unexpectedly fueled the momentum of the Laskar Walisongo movement. Despite the apparent weakening of the habaib's defensive stance, both the habaib and the Kyai Kampung have maintained considerable local influence. The ongoing power struggle highlights the complex interplay between belief, influence and control within this segment of the Sufi community. Ultimately, they have made public spaces an arena not just for collective imagery, but also the most vital part of the organisation’s sustainability or spirit.